Integrative lipidomic and transcriptomic study unravels the therapeutic effects of saikosaponins A and D on non-alcoholic fatty liver disease - Xiaojiaoyang Li; Junde Ge; Yajing Li; Yajie Cai; Qi Zheng; Nana Huang; Yiqing Gu; Qi Han; Yunqian Li; Rong Sun; Runping Liu (Elsevier, 2021)
Nonalcoholic fatty liver disease (NAFLD) has become one of the most prominent causes of chronic liver diseases and malignancies. However, few therapy has been approved. Radix Bupleuri (RB) is the most frequently used herbal medicine for the treatment of liver diseases. In the current study, we aim to systemically evaluate the therapeutic effects of saikosaponin A (SSa) and saikosaponin D (SSd), the major bioactive monomers in RB, against NAFLD and to investigate the underlying mechanisms. Our results demonstrated that both SSa and SSd improved diet-induced NAFLD. Integrative lipidomic and transcriptomic analysis revealed that SSa and SSd modulated glycerolipid metabolism by regulating related genes, like Lipe and Lipg. SSd profoundly suppressed the fatty acid biosynthesis by downregulating Fasn and Acaca expression and promoted fatty acid degradation by inducing Acox1 and Cpt1a expression. Bioinformatic analysis further predicted the implication of master transcription factors, including peroxisome proliferator-activated receptor alpha (PPARα), in the protective effects of SSa and SSd. These results were further confirmed in vitro in mouse primary hepatocytes. In summary, our study uncoded the complicated mechanisms underlying the promising anti-steatosis activities of saikosaponins (SSs), and provided critical evidence inspiring the discovery of innovative therapies based on SSa and SSd for the treatment of NAFLD and related complications.